Reducing post-harvest losses in an integrated way - Mahajan, BV C; Kapoor, Swati (Indian Horticulture, 2019)
Small marginalized farmers can gain extensively using integrated approach by initiating self-help group programmes. In this case, farmers could engage themselves in different activities as per their expertise and create a final product fit for marketing. Collective use of resources will help save a lot of money required for generating post-harvest management infrastructure. Some farmers can engage themselves in harvesting operations while other can engage themselves in sorting and grading activity and so on till the final produce is ready for marketing. The profit generated could then be divided equally amongst all. This strategy thus, holds the potential for generating both employment for rural youth and greater profit among the small land-holding farmers. The integrated approach such as harvesting, grading, waxing, packaging and storage not only help in reducing the postharvest losses but farmers and traders can get better price for their produce in market and consumers get better quality produce. Once the produce is properly graded and packed, the cost of final product is almost doubled in the retail market. Similarly, during peak harvesting season and glut like situation if the produce is stored under proper temperature and relative humidity conditions, the same produce fetches better price in the market.